The Role of Organizational Commitment and Work Stress on Nurse Performance - Mochammad Fatchurohman; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to determine the effect of Organizational Culture, Organizational Commitment, Work Stress and Burnout on the Performance of Nurses at the Siti Khodijah Muhammadiyah Hospital Sepanjang branch - Sidoarjo. This research includes quantitative research with hypothesis testing. The samples used in this study were 67 nurses at the Siti Khodijah Muhammadiyah Hospital Sepanjang branch - Sidoarjo. The analysis used is the multiple linear regression test ,F test, t test, multiple correlation coefficient test (R), and the coefficient of determination test (R2) which is tested using SPSS version 18.0 for windows. This primary data is obtained from a questionnaire whose test uses a Likert scale that is tested for validity and reliability and the data is declared valid and reliable. The results of this study prove that Organizational Culture, Organizational Commitment, Work Stress and Burnout simultaneously significantly influence Nurse’s Performance. Organizational Culture has a significant partial effect on Nurse Performance, Organizational Commitment has a Significant Partial effect on Nurse Performance, Work Stress has a Significant Partial effect on Nurse Performance, and Burnout has a Significant negative Partial effect on Nurse Performance. Besides the variable Organizational Commitment has the most significant influence on the performance of nurses at the Siti Khodijah Muhammadiyah Hospital Sepanjang branch - Sidoarjo.